Manhaj Kitāb Ta’lim Allughah Al’arabiyah Lilshafi Al awal Altsānawī" BAHASA ARAB MA KELAS X " Liwizārah Alsyu`ūn Aldīniyah Al Indūnīsiyah ām 2020 - Nurul Al Fudiah; Kristiana (Ukazh: Journal of Arabic Studies, 2022)
The interest in learning Arabic for non-native speaker in Indonesia has been increased as publishing of the Education Book by the Indonesian Ministry of Religion , because this book has a new appearance, and to improve and solve language problems, and to develop Arabic teaching in Islamic schools which are using this book, so this research aims to reveal its approach on curriculum of the Arabic education book by Ministry of Religious Affairs in 2020 “ BAHASA ARAB MA KELAS X “. The research used the qualitative and descriptive approach, analysing the Arabic language education book of the Ministry of Religious Affairs in 2020 on the evidence and the informations collected. The results obtained in this study suggest that curriculum of Arabic textbook of the Ministry of Religion “ BAHASA ARAB MA KELAS X “ was represented by the Religious Minister’s Resolution No. 183 of 2019 and aims to develop and prepare students can have abilities of cultural, communicative, and language competences, specially Arabic language . In teaching the elements of the Arabic language (Anashir al-lughah) the attention to phonology (Ashwat) was not intended, but it is included in the vocabulary and reading lesson, and in teaching Arabic skills (Maharat Lughawiyyah) in general, they were interested in the skill of listening, speaking, and reading, except for writing, as it was not sufficient in teaching it. The exercises in their presentation were good as it came with variety exercises, and in language tests didn’t use many types of tests. Minat pembelajaran bahasa Arab untuk penutur non-Arab di Indonesia telah meningkat dengan diterbitkannya Buku Ajar oleh Kementerian Agama Indonesia, karena sifat buku ajarnya yang baru dan untuk memperbaiki masalah yang ada, serta untuk mengembangkan pengajaran bahasa Arab di sekolah-sekolah yang menggunakan buku ini, maka penelitian ini bertujuan untuk mengungkap kurikulum Buku Ajar bahasa Arab Kementerian Agama tahun 2020 “ BAHASA ARAB MA KELAS X “ . Penelitian menggunakan pendekatan kualitatif, pengkajian pustaka, dan pendekatan deskriptif dimana peneliti menganalisis Buku Ajar bahasa Arab berdasarkan bukti dan informasi yang dikumpulkan. Adapun hasil penelitian, kurikulum Buku Ajar“ BAHASA ARAB MA KELAS X “ sebagai implementasi Keputusan Menteri Agama Nomor 183 Tahun 2019 bertujuan untuk mengembangkan dan membekali peserta didik memiliki kompetensi budaya, kompetensi komunikatif, dan kompetensi bahasa. Dalam pengajaran unsur-unsur bahasa Arab (Anashir al-Lughah), perhatian terhadap pelajaran bunyi (Ashwat) tidak secara khusus, tetapi termasuk dalam pembelajaran kosa kata dan membaca, dan dalam pengajaran keterampilan (Maharat Lughawiyyah) secara umum baik, keterampilan mendengarkan (Istima’), berbicara (Kalam), dan membaca (Qiraah), kecuali keterampilan menulis (Kitabah), dalam pengajarannya belum terbilang cukup. Dalam tugas-tugas latihan sudah bagus karena bervariasi. Sedangkan untuk tes bahasa tidak menggunakan beberapa macam jenis tes. لقد سما الاهتمام بتعلم اللغة العربية لغير الناطقين بها في إندونيسيا وهو بإصدار كتاب التعليم من قبل وزارة الشؤون الدينية، ولكونه حديثَ الظهور ولعلاج ما يحتاج إلى معالجته ولتطوير تعليم اللغة العربية يهدف هذا البحث إلى معرفة منهج كتاب تعليم اللغة العربية للصف الأول الثانوي لوزارة الشؤون الدينية الإندونيسية عام 2020 "”BAHASA ARAB MA KELAS 10 “. وجرت الباحثة في بحثها مستخدمة المدخل النوعي والمنهج المكتبي والوصفي حيث قامت بتحليل كتاب التعليم بناء على البينات والمعلومات المجمعة. أما نتيجة البحث أن منهج كتاب التعليم يتمثل لقرر الوزير الديني الرقم 183 السنة 2019 ويهدف تزويد الطلاب للحصول على الكفاءة الثقافية، والكفاءة الاتصالية، والكفاءة اللغوية. وفي تعليم عناصر اللغة العربية، الاهتمام بالأصوات لم يكن مخصصا ولكنه يضم في درس المفردات والقراءة، أما في تعليم المهارات عامة فهو به مهتم من مهارة الاستماع، والكلام، والقراءة، عدا الكتابة، فإنه لم يكن في تعليمها كافيا. والتدريبات في عرضها جيد حيث تأتي على التنوع. أما في الاختبارات اللغوية فهي غير مستعينة بعدة أنواع الاختبار